2022
DOI: 10.1101/2022.12.10.519857
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

eEF2 improves dense connective tissue repair and healing outcome by regulating cellular death, autophagy, apoptosis, proliferation and migration

Abstract: Outcomes following human dense connective tissue (DCT) repair are often variable and suboptimal, resulting in compromised function and development of chronic painful degenerative diseases. Moreover, biomarkers and mechanisms that guide good clinical outcomes after DCT injuries are mostly unknown. Here, we characterize the proteomic landscape of DCT repair following human tendon rupture and its association with long-term patient-reported outcome. Moreover, the regulatory mechanisms of relevant biomarkers were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…Autophagy can eliminate cel- There is a close relationship between autophagy and tissue repair. 41 Briefly, autophagy participates in the clearance of intracellular waste and the recycling of metabolic products, which can provide necessary nutrients for damaged tissues and promote tissue repair. 42 Ma and colleagues have found that inducing autophagy leads to more labeled MSCs migrating to the site of injury.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy can eliminate cel- There is a close relationship between autophagy and tissue repair. 41 Briefly, autophagy participates in the clearance of intracellular waste and the recycling of metabolic products, which can provide necessary nutrients for damaged tissues and promote tissue repair. 42 Ma and colleagues have found that inducing autophagy leads to more labeled MSCs migrating to the site of injury.…”
Section: Discussionmentioning
confidence: 99%